Genetic screening confirms heterozygous mutations in ACAN as a major cause of idiopathic short stature - Hauer, Nadine; Sticht, Heinrich; Boppudi, Sangamitra; Büttner, Christian; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; Abou Jamra, Rami; Wieczorek, Dagmar; Kelkel, Jaqueline; et al. (Scientific Reports, 2017)
Short stature is a common pediatric disorder affecting 3% of the population. However, the clinical variability and genetic heterogeneity prevents the identification of the underlying cause in about 80% of the patients. Recently, heterozygous mutations in the ACAN gene coding for the proteoglycan aggrecan, a main component of the cartilage matrix, were associated with idiopathic short stature. To ascertain the prevalence of ACAN mutations and broaden the phenotypic spectrum in patients with idiopathic short stature we performed sequence analyses in 428 families. We identified heterozygous nonsense mutations in four and potentially disease-causing missense variants in two families (1.4%). These patients presented with a mean of -3.2 SDS and some suggestive clinical characteristics. The results suggest heterozygous mutations in ACAN as a common cause of isolated as well as inherited idiopathic short stature.
EVALuna2:9379